New records of alien polychaete species for the coasts of Turkey - CINAR, M.E.; DAGLI, E. (Mediterranean Marine Science, 2012)
This paper reports two alien polychaete species (Phyllodoce longifrons and Exogone africana) new to the faunal inventory of Turkey as well as two species (Ceratonereis mirabilis and Onuphis eremita oculata) new to the entire Aegean Sea. It is the first time the phyllodocid species P. longifrons is being classified as an alien species. The re-descriptions of P. longifrons and E. africana are given, and their alien status and establishment success are discussed.